2011
DOI: 10.1091/mbc.e10-08-0668
|View full text |Cite
|
Sign up to set email alerts
|

Histone and TK0471/TrmBL2 form a novel heterogeneous genome architecture in the hyperthermophilic archaeonThermococcus kodakarensis

Abstract: This study demonstrates that the chromosome of the hyperthermophilic archaeon Thermococcus kodakarensis is organized into a heterogeneous structure created with histone and a novel protein TK0471/TrmBL2. TK0471/TrmBL2 plays dual roles as a chromosomal protein and as a global transcriptional repressor, and it is conserved in some archaeal and bacterial species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(100 citation statements)
references
References 48 publications
(56 reference statements)
6
92
1
1
Order By: Relevance
“…For Tco. kodakarensis TrmBL2 (TK0471), a role as an abundant chromosomal protein, which forms fibrous, thick structures with DNA, was reported (489). TrmBL2 binds to coding and intergenic regions of the DNA and thus probably represses transcription by blocking RNAP recruitment.…”
Section: Fig 20mentioning
confidence: 99%
“…For Tco. kodakarensis TrmBL2 (TK0471), a role as an abundant chromosomal protein, which forms fibrous, thick structures with DNA, was reported (489). TrmBL2 binds to coding and intergenic regions of the DNA and thus probably represses transcription by blocking RNAP recruitment.…”
Section: Fig 20mentioning
confidence: 99%
“…Band shift experiments revealed that it binds to the TGM sequence with low affinity but not exclusively [3]. For the highly homologous TK0471 protein from T. kodakarensis [8,9], it was shown to bind nonspecifically to DNA and impart on it the appearance of a thick, stiff fiber.…”
Section: Discussionmentioning
confidence: 99%
“…This staggered arrangement of the dimers on the DNA ensures a larger coverage of the DNA surface that, along with its nonspecific binding mode, could hinder access to various DNA modifying enzymes [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations